Pengaruh Shoppertainment Terhadap Keputusan Pembelian Pada Media Sosial TikTok - Beatriz Beatriz; Monica Anastasia; Erica Adriana (Institut Nalanda, 2023)
Digital marketing allows consumers to connect directly with business owners through social media accounts. One of the social media that is trending or popular and most downloaded by Indonesians is the TikTok application. This type of research in this study uses a literature study. Literature study is carried out by collecting references consisting of several previous studies which are then put together to draw conclusions. The results of this study indicate that shoppentertaiment on live streaming has a positive effect on purchasing decisions. Through live streaming consumers can see products in real time, also get more complete information about product details and have the opportunity to interact through direct comments with the seller.